(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Endometriosis is a benign chronic disease, characterized by the presence and proliferation of functional endometrial gland and stroma outside the uterine cavity. Objective: To evaluate the usefulness of intracellular adhesion molecule-1 (ICAM-1) and Glycodelin (Gd) as a biomarker for the diagnosis of endometriosis and to help in detection of various stages of endometriosis. Methods: Forty-four patients with endometriosis and 35 apparently healthy women as control were enrolled in this study from November 2015 to April 2016. All individuals were subjected to blood sampling for measuring their serum ICAM-1 and Gd A level by using enzyme linked immune sorbent assay technique. Results: The current study revealed significantly higher serum levels of ICAM-1 and Gd in patients group in comparison with healthy control. In addition, the sensitivity and specificity for ICAM-1 and Gd A in serum were 61%/ 66%, 76%/ 85% respectively. Conclusion: The ICAM-1 and Gd A level in serum may be useful as noninvasive test for diagnosis of endometriosis in all stages. Keywords: Endometriosis, ICAM-1, Glycodelin Citation: Draj HA, Abbas AA, Abdullah TH. Serum levels of Glycodelin A and Soluble Intracellular Adhesion Molecule-1 as biomarkers for endometriosis. Iraqi JMS. 2017; Vol. 15(4): 345-349. doi: 10.22578/IJMS.15.4.4